(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The focus of the problem in this study is to identify the effect of earnings quality on the company’s cash holdings. In this context, earnings quality as measured by accrual quality and earnings persistence will be analyzed to see whether companies with high-quality earnings have more efficient cash management compared to companies with low-quality earnings. This study was conducted using a purposive sampling method. The population in this study were all consumer goods sector companies listed on the Indonesia Stock Exchange (IDX). All data are sourced from the company’s annual financial reports available on the official website of the Indonesia Stock Exchange (https://www.idx.co.id) and the official websites of each company. The data collection method for this study was carried out by documentation and literature study. The data analysis method uses descriptive statistics, classical assumption tests and hypothesis testing. The test results show that earnings quality as proxied by accrual quality has a positive but insignificant effect on cash holdings of consumer goods manufacturing companies on the IDX. Conversely, earnings persistence has a significant negative effect, indicating that the lower the earnings persistence, the higher the cash holdings. Firm size has a positive effect, indicating that large firms tend to hold more cash for operational needs. Meanwhile, leverage has a negative effect, because high debt reduces available cash.